Vancomycin pharmacokinetics in patients treated with intermittent haemodialysis based on therapeutic drug monitoring - Hartinger, Jan Miroslav; Šíma, Martin; Hronová, Karolína; Halouzková, Barbora Agátha; Szonowská, Barbora; Polakovič, Vladimír; Bednářová, Vladimíra; Hladinová, Zuzana; Tesař, Vladimír; Slanař, Ondřej (Journal of chemotherapy (Florence, Italy), 2022)
Vancomycin is frequently used in haemodialysis (HD) patients but generally accepted target serum ranges and dosing strategy are still lacking in this group. Based on retrospective analysis of data from 118 HD patients treated with vancomycin the interdialytic elimination constant (Ke), apparent volume of distribution (Vd) and dialysis efficacy were calculated. The influence of possible clinical variables on the pharmacokinetic parameters of vancomycin have been tested. The median of Ke in interdialytic periods, corresponding half-life and Vd were 0.0073 h-1, 95.0 h and 0.87 L/kg, respectively. We found significant positive correlation between time in dialysis program and Ke. The Vd correlated best with lean body mass (LBM). For high- and low flux membrane HD of 4 hours duration the decline in vancomycin levels was 20.88% and 12.86%, respectively. Based on these data loading dose for vancomycin in HD patient should be calculated as 24.483 × LBM (kg) + 455 mg. The utility of this equation for entire HD population should be also verified prospectively.
Keywords: therapeutic drug monitoring; poločas; Half-Life; Renal Dialysis; vankomycin; monitorování léčiv; dialýza ledvin; Drug Monitoring; retrospektivní studie; Anti-Bacterial Agents; Humans; haemodialysis; pharmacokinetics; Vancomycin; Retrospective Studies; lidé; antibakteriální látky; dosing